Ultrastructural patterns of the excretory ducts of basal neodermatan groups (Platyhelminthes) and new protonephridial characters of basal cestodes - Poddubnaya, Larisa G; Kuchta, Roman; Scholz, Tomáš (Parasites & vectors, 2020)
BACKGROUND: The flatworms (Lophotrochozoa: Platyhelminthes) are one of the major phyla of invertebrates but their interrelationships are still not well understood including unravelling the most closely related taxon of the Neodermata, which includes exclusively obligate parasites of all main groups of vertebrates with some 60,000 estimated species. Recent phylogenomic studies indicate that the freshwater 'microturbellarian' Bothrioplana semperi may be the closest ancestor to the Neodermata, but this hypothesis receives little morphological support. Therefore, additional morphological and ultrastructural characters that might help understand interrelations within the Neodermata are needed. METHODS: Ultrastructure of the excretory ducts of representatives of the most basal parasitic flatworms (Neodermata), namely monocotylid (Monopisthocotylea) and chimaericolid (Polyopisthocotylea) monogeneans, aspidogastreans (Trematoda), as well as gyrocotylidean and amphilinidean tapeworms (Cestoda), were studied using transmission electron microscopy (TEM). RESULTS: The present study revealed the same pattern of the cytoarchitecture of excretory ducts in all studied species of the basal neodermatans. This pattern is characterised by the presence of septate junctions between the adjacent epithelial cells and lateral ciliary flames along different levels of the excretory ducts. Additionally, a new character was observed in the protonephridial terminal cell of Gyrocotyle urna, namely a septate junction between terminal and adjacent duct cells at the level of the distal extremity of the flame tuft. In Amphilina foliacea, a new type of protonephridial cell with multiple flame bulbs and unique character of its weir, which consists of a single row of the ribs, is described. A remarkable difference has been observed between the structure of the luminal surface of the excretory ducts of the studied basal neodermatan groups and B. semperi. CONCLUSIONS: The present study does not provide ultrastructural support for a close relationship between the Neodermata and B. semperi.
Keywords: Animals; Microscopy, Electron, Transmission; ploštěnci; Phylogeny; Trematoda; Platyhelminths; transmisní elektronová mikroskopie; zvířata; biologická evoluce; Biological Evolution; fylogeneze; Cestoda